Reconstruction of the Ijārah Contract ‘Alā Al-Manāfi’ in the Practice of Stall Rental in Sigli City Square: Analysis of Fairness in Pricing and Trader Protection - Rayyani Azzahra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines the practice of stall rental agreements at the Sigli City Square, Pidie Regency, Aceh, with a focus on the conformity between the concept of ijārah ‘alā al-manāfi’ in Islamic jurisprudence and its implementation in practice. The main issue lies in the discrepancy between normative principles and empirical realities. Normatively, the rental practice has fulfilled the essential elements of the contract, including the existence of clear benefits, a determined rental price, and mutual agreement between the parties. However, in practice, several weaknesses are identified, such as agreements conducted orally and tend to be unilateral without negotiation, as well as the application of a fixed daily rental fee of Rp5,000, locally known as “uang adat,” without considering differences in stall size or space. This condition potentially creates an imbalance between the benefits received and the payment made, thereby raising issues of fairness within the contract. This research employs a normative-empirical approach with a field research design. Data were collected through observation and interviews with traders and officials from the Department of Trade and Cooperatives of Pidie, supported by literature studies on Islamic jurisprudence, DSN-MUI Fatwa No. 112/DSN-MUI/X/2017, and Qanun Pidie No. 26/2011. The data were analyzed descriptively by comparing empirical practices with normative provisions. The findings indicate that, normatively, the rental practice is valid and in line with the concept of ijārah ‘alā al-manāfi’, particularly from the perspectives of the Hanafiyah and Malikiyah schools. However, its implementation has not fully reflected the principle of fairness due to the absence of standards that consider differences in benefits. Therefore, improvements are needed through written agreements, standardization of stall sizes, and better management practices to achieve optimal public welfare